2008
DOI: 10.1074/jbc.m804417200
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Mechanism Controls Redox-mediated Protein-DNA Interactions at the Replication Origin of Kinetoplast DNA Minicircles

Abstract: Kinetoplast DNA (kDNA) is the mitochondrial DNA of trypanosomatids. Its major components are several thousand topologically interlocked DNA minicircles. Their replication origins are recognized by universal minicircle sequence-binding protein (UMSBP), a CCHC-type zinc finger protein, which has been implicated with minicircle replication initiation and kDNA segregation. Interactions of UMSBP with origin sequences in vitro have been found to be affected by the protein's redox state. Reduction of UMSBP activates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 52 publications
1
22
1
Order By: Relevance
“…Most notably, no defects in kinetoplast morphology and division were noticed (Figure 1E). These observations argue against the involvement of mTXNPx in kDNA replication, a function previously attributed to mitochondrial TXNPxs [20], [22]. Even though these results indicate that mTXNPx is redundant in the insect form of L. infantum , they do not discard a relevant role for this enzyme during the amastigote stage.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…Most notably, no defects in kinetoplast morphology and division were noticed (Figure 1E). These observations argue against the involvement of mTXNPx in kDNA replication, a function previously attributed to mitochondrial TXNPxs [20], [22]. Even though these results indicate that mTXNPx is redundant in the insect form of L. infantum , they do not discard a relevant role for this enzyme during the amastigote stage.…”
Section: Resultscontrasting
confidence: 61%
“…UMSBP binds to the DNA when it is reduced and is released when oxidized. According to the proposed model, mTXNPx would oxidize UMSBP [20].…”
Section: Introductionmentioning
confidence: 99%
“…UMSBP is a zinc finger protein that plays a key role in the replication of mitochondrial DNA in trypanosomatids. The binding of UMSBP to the kinetoplast DNA is significantly affected by the redox state and Tpx has been shown to act as the reducing agent (161,164,179,220). MSRs are involved in protein repair by catalyzing the reduction of methionine sulfoxide residues to methionine.…”
Section: Many Reactions Of Trypanothione Are Mediated By Tpxmentioning
confidence: 99%
“…Formaldehyde was added to a final concentration of 1%, and the reaction mixture was incubated for additional 5 min at 25°C, followed by its 5-fold dilution in triple-distilled water. Then, loading buffer was added, and the protein samples were electrophoresed in 16.5% polyacrylamide gel, as described previously (10).…”
Section: Methodsmentioning
confidence: 99%
“…Minicircle replication initiates at conserved origin sequences, which are bound by a mitochondrial singlestranded sequence-specific DNA-binding protein, named the universal minicircle sequence-binding protein (UMSBP) (4 -9). UMSBP is a CCHC-type zinc finger protein whose binding to origin sequences is regulated by the cell cycle control of the protein redox state (10,11). Cross-linking analysis has shown that UMSBP binds the kDNA network in vivo (8).…”
mentioning
confidence: 99%